Summer Outbreak of Severe RSV-B Disease, Minnesota, 2017 Associated with Emergence of a Genetically Distinct Viral Lineage. (20th February 2020) - Thielen, Beth K; Bye, Erica; Wang, Xiong; Maroushek, Stacene; Friedlander, Hannah; Bistodeau, Sarah; Christensen, Jaime; Reisdorf, Erik; Shilts, Meghan H; Martin, Karen; Como-Sabetti, Kathryn; Strain, Anna K; et al.
Abstract: Background: Respiratory syncytial virus (RSV) typically causes winter outbreaks in temperate climates. During summer 2017, the Minnesota Department of Health received a report of increased cases of severe RSV-B infection. Methods: We compared characteristics of summer 2017 cases with those of 2014–2018 summers. To understand the genetic relatedness among viruses, we performed high-throughput sequencing of RSV from patients with a spectrum of illness from sites in Minnesota and Wisconsin. Results: From May to September 2017, 58 RSV cases (43 RSV-B) were reported compared to 20–29 cases (3–7 RSV-B) during these months in other years. Median age and frequency of comorbidities were similar, but 55% (24/43) were admitted to the ICU in 2017 compared to 12% in preceding 3 years (odds ratio, 4.84, P < .01). Sequencing was performed on 137 specimens from March 2016 to March 2018. Outbreak cases formed a unique clade sharing a single conserved nonsynonymous change in the SH gene. We observed increased cases during the following winter season, when the new lineage was the predominant strain. Conclusions: We identified an outbreak of severe RSV-B disease associated with a new genetic lineage among urban Minnesota children during a time of expected low RSV circulation. Abstract : We describe use of whole-genome sequencing to identify viral genetic features associated with an increased number and severity of respiratory syncytial virus cases among children and adults in Minnesota.